A rare case report of ovarian juvenile granulosa cell tumor with massive ascites as the first sign, and review of literature: Case report and review of literature. Issue 25 (June 2018) - Ma, Liang; Zhang, Liwen; Zhuang, Yun; Ding, Yanbo; Chen, Jianping
Abstract: Rationale: Massive ascites as the first sign of ovarian juvenile granulosa cell tumor (JGCT) in an adolescent is an extremely rare, and its clinical features and treatment methods have not been well described. Patient concerns: The clinical characteristics, diagnosis, and treatment methods in a 19-year-old girl who presented with massive abdominal distention and ascites was retrospectively reviewed. Abdominopelvic ultrasonography showed a large amount of ascites. The nature of ascites was exudate. All tumor markers were normal, but ascites and serum tumor CA125 levels were significantly increased. Abdominal CT showed left attachment area teratoma and right attachment area capsule solid change. Diagnoses: Histological and immunohistochemical results were compatible with JGCT. Based on the FIGO classification, the patient with only malignant ascites was categorized into stage IC. Interventions: The patient underwent mass resection with salpingoophorectomy. Following the operation, she received 6 courses of adjuvant chemotherapy with Nedaplatin and Paclitaxel liposome. Outcomes: The patient was followed up postoperatively for 6 months to date without recurrence. Lessons: We should be highly vigilant the JGCT with massive ascites as the first clinical manifestation.